Phenotype and Physiological Significance of the Endocardial Smooth Muscle Cells in Human Failing Hearts. (January 2015) - Okada, Hideshi; Takemura, Genzou; Kanamori, Hiromitsu; Tsujimoto, Akiko; Goto, Kazuko; Kawamura, Itta; Watanabe, Takatomo; Morishita, Kentaro; Miyazaki, Nagisa; Tanaka, Toshiki; Ushikoshi, Hiroaki; Kawasaki, Masanori; et al.
<x xml:space="preserve">Abstract</x> Background— Extravascular smooth muscle cells are often observed in the endocardium of human failing hearts. Here, we characterized the phenotype of those cells and investigated their physiological significance. Methods and Results— We examined left ventricular biopsy specimens obtained from 44 patients with dilated cardiomyopathy and 6 nonfailing hearts. In Masson trichrome–stained histological preparations, bundles of smooth muscle cells were seen localized in the endocardium in 23 of the 44 specimens (none of the 6 controls). These cells were immunopositive for α-smooth muscle actin, type 2 smooth muscle myosin, desmin, and calponin, but were negative for embryonic smooth muscle myosin, vimentin, fibronectin, and periostin. This profile is indicative of a late differentiation (contractile) smooth muscle phenotype. Electron microscopy confirmed that phenotype, revealing the cells to contain abundant myofilaments with dense bodies but little rough endoplasmic reticulum or Golgi apparatus. In the endocardial smooth muscle–positive group, the left ventricular end-systolic volume index (73±34 versus 105±50 mL/m2; P=0.021), left ventricular peak wall stress (164±47 versus 196±43 dynes 103/cm2; P=0.023), and left ventricular end-systolic meridional wall stress (97±38 versus 121±37 dynes 103/cm2; P=0.036) were all significantly smaller, and the ejection fraction was larger (41±8.8 versus 33±9.3%; P=0.005) than in the endocardial smooth muscle–negative group. However, no histological parameters differed between the 2 groups. Conclusions— Endocardial smooth muscle cell bundles in hearts with dilated cardiomyopathy exhibit a mature contractile phenotype and may play a compensatory role mitigating heart failure by reducing left ventricular wall stress and systolic dysfunction.